Nilai dan Fungsi Upacara Tumbuk Erdemu Bayu Bagi Masyarakat Muslim Karo Sebagai Tanda Pernikahan di Kabupaten Karo - Bangun, Anisah Br; Ritonga, Sakti (Jurnal Community, 2024)
The purpose of this article is to describe the value and function of the “Tumbuk Erdemu Bayu” ceremony for the Karo Muslim community in Sukajulu Village, Barusjahe Sub-district, Karo District. This research uses a qualitative method with a phenomenological approach. Data collection techniques were obtained by using interviews, observation, and documentation. Thise focus of this research, will explore more deeply how the Value and Function of the “Tumbuk Erdemu Bayu” ceremony for the Karo Muslim community in Sukajulu Village. Then the data is processed and analyzed descriptively. The results of this study indicate that the value of the traditional wedding ceremony “Tumbuk Erdemu Bayu” for the Karo Muslim Community in Sukajulu is as a legitimization of the validity of a marriage according to customary law and as a sign of social identity and recognition for them that the Muslim community will remain part of them even though Islam is a minority religion in the village. The “Tumbuk Erdemu Bayu” ceremony also has a function as a sign of unity among interfaith communities, fostering harmony within the community, as a medium for cultural preservation, as a strengthening of individual identity in traditional culture and as a binding kinship relationship.